Interaction of Listeria monocytogenes with Human Brain Microvascular Endothelial Cells: an Electron Microscopic Study - Greiffenberg, Lars (American Society for Microbiology, 2000)
Internalization of Listeria monocytogenes into human brain microvascular endothelial cells (HBMEC) has recently been demonstrated to be dependent upon the inlB gene. In the present scanning electron microscopic study we show that L. monocytogenes efficiently interacts with the surface of HBMEC in an inlB-independent manner which is also different from invasion. The inlB-dependent invasion of HBMEC by L. monocytogenes is accompanied by intracellular multiplication, movement, and production of bacterium-containing protrusions. These protrusions extend from the cell surface without perturbation of any adjacent cellular membrane.